P–519 Investigation of embryo chromosomal constitution and live birth rate after vitrified-warmed euploid single blastocyst transfer across ranges of maternal body-mass-index. (6th August 2021) - Fabozzi, G; Cimadomo, D; Allori, M; Vaiarelli, A; Colamaria, S; Argento, C; Amendola, M G; Innocenti, F; Soscia, D; Maggiulli, R; Mazzilli, R; Marchetti, M; et al.
Abstract: Study question: Does maternal body-mass-index (BMI) associate with blastocysts' chromosomal constitution and clinical outcomes in infertile patients undergoing preimplantation genetic testing for aneuploidies (PGT-A)? Summary answer: A higher euploidy rate per biopsied blastocyst was reported among underweight women. Overweight women were instead subject to higher miscarriage (MR) and lower live-birth-rates (LBR). What is known already: Different studies in the literature revealed an association between BMI and infertility, suggesting a J-shaped relationship: both underweight and overweight women can suffer from infertility issues. Even if IVF might increase the success rate in both these categories of patients, it seems insufficient per se to overcome the complex and multifactorial fertility impairment derived from unbalanced nutritional intakes. Miscarriage, in particular, is common in both underweight and overweight women. However, most of the literature is based on chromosomally-untested embryos. Study design, size, duration: Retrospective observational study. Only the first IVF cycle with ≥1 biopsied blastocyst from each woman was included. The primary outcome was the association between maternal BMI (underweight, BMI<18.5, n = 160; normal-weight, BMI=18–25, N = 1392; overweight, BMI>25, N = 259) and the mean euploidy rate per cohort of biopsied blastocysts (m-ER). The secondary outcomes were the association between maternal BMI with clinical (mainly MR and LBR), gestational and perinatal outcomes after first vitrified-warmed single euploid blastocyst transfers. Participants/materials, setting, methods: We included 1811 women undergoing PGT-A at a private IVF center between April–2013 and March–2020. The secondary outcomes were investigated on 1125 first vitrified-warmed single euploid blastocyst transfers from all patients obtaining ≥1 transferable blastocyst. Only ICSI with ejaculated sperm and continuous culture in standard incubators were performed. Logistic regressions were conducted to identify putative confounders and adjust the results accordingly. Main results and the role of chance: Except for a lower maternal age among underweight women (38.3±3.1 versus 38.9±3.4 yr, p < 0.01) and higher among overweight ones (39.3±3.6 yr, p = 0.04), no difference was reported with respect to normal-weight women in terms of duration of infertility, hormonal levels, main cause of infertility, sperm quality, and reproductive history. The mean number of biopsied blastocysts was ∼3 in all groups. The m-ER shows a decreasing trend as the maternal BMI increases between 17 and 22–23, to then plateau. In fact, a significant difference was reported between underweight (50.8%±36.4%) and normal-weight women (41.4%±37.5%, p < 0.01). A linear regression adjusted for maternal age confirmed this moderate association between increasing BMI and m-ER (unstandardized-coefficient-B –0.6%, 95%CI:–1.1% to –0.1%, p = 0.02). Morphological quality and day of full-blastulation among transferred euploid blastocysts was similar in the three groups. Overweight women showed higher MR per pregnancy (N = 20/75, 26.7%, 95%CI:17.4%–38.3% versus N = 67/461, 14.5%, 95%CI:11.5%–18.2%; OR 2.0, 95%CI:1.1–3.6, p = 0.01) and lower LBR per transfer (N = 55/154, 35.7%, 95%CI:28.3%–43.8% versus N = 388/859, 45.2%, 95%CI:41.8%–48.6%; OR adjusted for euploid blastocysts' features 0.67, 95%CI:0.46–0.96, p = 0.03). Clinical outcomes were instead similar among underweight and normal-weight women. All gestational and perinatal outcomes were comparable in the tree groups. Limitations, reasons for caution: Our study is limited by its retrospective nature, and the fact that maternal BMI was measured only before oocyte retrieval and not before embryo transfer. Moreover, the reduced sample size did not allow for further relevant sub-analyses among solely obese women. Wider implications of the findings: When possible nutritional/lifestyle modifications should be encouraged to adjust maternal BMI before IVF. Overweight patients should be especially informed of their higher risk for miscarriage. Yet, BMI is just a gross marker, future studies based on body fat localization and percentage (e.g. by bioelectrical impedance analyses) are desirable. Trial registration number: None